PENYELENGGARAAN PAI PADA SLB DI JAWA TIMUR (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
AbstractThe purpose of this research is to acquire an objective and comprehensive information about the implementation of Islamic religion teaching and learning process for special school for special care children. Result of the research finds that special schools have done Islam religion teaching learning process so far besides, it has found that most of the teachers of Islamic religion at special school (SLB) are not teacher with the qualification of Islam religion background (PGA and Tarbiyah) teacher training. But with the background of special school teacher training background (SGPLB and LPTK PLB). The teaching learning process PAI at special school generally runs normativelly. The efforts to supervise and develop the competence and profession of Islam religion teacher at special school are still considered insufficient, got in its supervision and its control. Those who are supposed to be involved supervising the teacher od Islam religion at special schools are department of religion, department of National Education (provincial office) and controllers on the executors in the field, herve not played optimal role yet.Â
Keywords: Islam religion; special school (SLB)